1997
DOI: 10.1023/a:1024834330300
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The authors describe the prevalence of childhood traumatic experiences among adolescent inpatients. A Childhood Trauma Chart Review Scale (CTCRS) was developed to assess traumatic experiences during childhood and adolescence. The CTCRS was reliably applied to the medical records of 75 adolescent inpatients who had been given structured clinical interviews for DSM-III-R diagnoses at the time of admission. Most subjects (81%) had experienced at least one traumatic event during childhood, with loss of caregiver b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Davidson and Smith [22] reported that PTSD was three times more likely to develop when traumatic events were experienced before the age of 11 years. Lastly, Weine et al [23] studied 75 male and female adolescent inpatients aged 13 -18 years and found that 81% reported experiencing at least one traumatic event in childhood. The loss of a parent or caregiver was the most frequent type of trauma reported.…”
mentioning
confidence: 99%
“…Davidson and Smith [22] reported that PTSD was three times more likely to develop when traumatic events were experienced before the age of 11 years. Lastly, Weine et al [23] studied 75 male and female adolescent inpatients aged 13 -18 years and found that 81% reported experiencing at least one traumatic event in childhood. The loss of a parent or caregiver was the most frequent type of trauma reported.…”
mentioning
confidence: 99%